Corruption In The Colonial Period: Social Criticism Of The Indigenous Elite In Max Havelaar (1976) - Raja Guk Guk, Justin; Purba, Defitri; Mutiara, Layla; Wahyuni, Hidayah; Hasanah, Nur; Sarida, Sarida; Lita Purba, Angel (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2026)
This study discusses corruption during the colonial period as portrayed in the film Max Havelaar (1976), focusing on social criticism toward the role of indigenous elites. The aim of this research is to explain how the film presents corruption as part of the colonial power system involving cooperation between colonial authorities and local elites. This study uses a qualitative method through a literature review and film analysis. The analysis applies Stuart Hall’s Representation Theory, Antonio Gramsci’s social criticism theory, and Homi K. Bhabha’s postcolonial theory. The findings show that corruption in the film is not only carried out by colonial rulers but also involves indigenous elites who act as intermediaries of power. This research contributes to understanding the historical roots of corruption through film as a medium of social criticism and historical reflection.